Targeted Multidrug Resistant Organism Antimicrobial Prophylaxis and Postoperative Infections in Pediatric Cardiothoracic Surgical Patients. Issue 6 (June 2020) - Cies, Jeffrey J.; Palladino, Christina; Mahmood, Hera; Moore, Wayne S.; Chopra, Arun
Abstract : Background: To determine if receiving targeted antimicrobial (AM) prophylaxis has an effect on the rate of postoperative infections in patient's colonized with a multidrug resistant organism (MDRO) undergoing cardiothoracic surgery (CTS). Methods: Single-center, retrospective medical record review of pediatric patients from birth to 18 years of age undergoing CTS from January 2013 to September 2018. Demographic data collected included age, specific MDRO, site of MDRO colonization, type of surgery, perioperative AM agent and type of infection. Patients were stratified into 2 groups, MDRO+ and MDRO–. Demographic and clinical characteristics were compared between groups with a Student's t test for continuous variables and a χ2, Fisher exact test or Mann–Whitney U test for noncontinuous variables. A 2-sided significance level of α = 0.05 was used to determine statistical significance. All analyses were performed using IBM SPSS Version 24 (SPSS Inc., Chicago, IL). Results: Fifty patients (26 males/24 females) were included in the MDRO (+) group and 295 patients (168 males/127 females) in the MDRO (–) group. The median age was 0.48 years (interquartile range 0.24–1 year) and 0.9 years (interquartile range 0.19–8 years) in the MDRO (+) and MDRO (–) groups, P = 0.003. 2 of 50 (4%) MDRO (+) patients and 15 of 295 (5.1 %) MDRO (–) patients developed an infection, P = 1. 10 of 50 (20%) MDRO (+) patients received targeted AM toward the MDRO and none developed an infection. Of the 2 MDRO (+) patients with infection, 1 was infected with the MDRO. For MDRO (+) patients, there was no difference in the rate of infection whether targeted AM therapy was received, P = 1. Conclusions: There was no difference in the rate of postoperative infection between MDRO (+) and MDRO (–) patients. Additionally, these preliminary pediatric data suggest targeting AM agents to a specific MDRO does not impact the rate of postoperative infection in children undergoing CTS. Larger studies are warranted to confirm these findings.